Teachers’ Expectations from their University: A Study in the Context of University of Lucknow - M. Varma,; M.s. Sodha,; Rashmi Soni, (JOURNAL OF INDIAN EDUCATION, 2025)
Teachers’ Expectations from various dimensions of the University of Lucknow were studied by descriptive method and classified. Teachers were engaged in open conversational interview which was recorded and afterwards subjected to content analysis which yielded 27 categories of expectations which were further classified on the basis of similarities and dissimilarities into ten broad classes of expectations which have been discussed in this paper. Findings showed that the university teachers expected reforms in admission and examination system. Also, they suggested modifications in the methods of teaching, dealing with indiscipline and the present activities of associations of teachers, students and the employees. They expected upgradation of infrastructure and resources in the university especially in the areas of library, laboratory, hostel, teachers’ residences and facilities in the departments. Results indicated the expectations of university teachers’ to redefine the role of university in present global scenario and to review the role of vice chancellor, other officers of university, administration and duties of teachers. Several conflicting expectations were also obtained which have been discussed in the paper. The study of Teachers’ Expectations from university has indicated need of reforms in the university on which the policy-makers and the stakeholders should focus their attention. The paper has suggested that periodically the study of expectations from the university should be undertaken if the stakeholders desire to make the University of Lucknow capable and useful in the fast changing scenario of Higher education in India and abroad.